Assessment of aquatic plants in the reservoirs of AES-Tiete and development of an integrated control model for the most important species - Velini, Edivaldo Domingues [UNESP]; Galo, MLBT; Carvalho, F. T.; Martins, D.; Cavenaghi, A. L.; Trindade, MLB; Bravin, LFN; Negrisoli, E.; Antuniassi, Ulisses Rocha [UNESP]; Simionato, JLA; Santos, SCA (Marcel Dekker Inc, 2005)
The general objective of this work was to develop a monitoring and management model for aquatic plants that could be used in reservoir cascades in Brazil, using the reservoirs of AES-Tiete as a study case. The investigations were carried out at the reservoirs of Barra-Bonita, Bariri, Ibitinga, Promissao, and Nova-Avanhandava, located in the Tiete River Basin; Agua Vermelha, located in the Grande River Basin; Caconde, Limoeiro, and Euclides da Cunha, which are part of the Pardo River Basin; and the Mogi-Guacu reservoir, which belongs to the Mogi-Guacu River basin. The main products of this work were: development of techniques using satellite-generated images for monitoring and planning aquatic plant control; planning and construction of a boat to move floating plant masses and an airboat equipped with a DGPS navigation and application flow control system. Results allowed to conclude that the occurrence of all types of aquatic plants is directly associated with sedimentation process and, consequently, with nutrient and light availability. Reservoirs placed at the beginning of cascades are more subject to sedimentation and occurrence of marginal, floating and emerged plants, and are the priority when it comes to controlling these plants, since they provide a supply of weeds for the other reservoirs. Reservoirs placed downstream show smaller amounts of water-suspended solids, with greater transmission of light and occurrence of submerged plants.
Keywords: remote sensing; aquatic plants; weed mapping; integrated management